Biosafety of Campylobacter jejuni from raw vegetables consumed as ulam with reference to their resistance to antibiotics - Chai, Lay Ching; Abu Bakar, Fatimah; Mohamad Ghazali, Farinazleen; Lee, Hai Yen; Robin, Tunung; Abdul Talib, Shamsinar; Ahmad Suhaimi, Laila Rabaah; Zakaria, Thahirahtul Asma; Malakar, Pradeep Kumar; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
Antibiotic resistance in campylobacter is an emerging global public health problem after MRSA and VRE. Fluoroquinolone and macrolide resistance have been found to be more common in this world leading foodborne pathogen. A total of fifty-six isolates of Campylobacter jejuni obtained from raw vegetables which are consumed as ulam (salad) in Malaysia, were tested with 12 antibiotics used clinically and agriculturally. The resistance was determined using the disk diffusion method. Results were determined by hierarchic numerical methods to cluster strains and antibiotics according to similarity profiles. Fifty five C. jejuni isolates from different isolation sites were all clustered together into ten groups. This indicates that the commodities (raw salad vegetables/ulam) where the isolates originated might share a similar source of cross-contamination along the production route. All antibiotics tested correlated and there were four groupings reflecting their mode of actions. Generally, C. jejuni isolates were found to be highly resistant to erythromycin (91.1%) and tetracycline (85.7%). Both agents are popular antibiotics used clinically to treat bacterial infections. On the other hand, the C. jejuni isolates showed high percentage (80.4%) of resistance towards enrofloxacin, an extensively used antimicrobial agent in agriculture practices. This study showed that C. jejuni isolates were highly multi-resistance to as many as 10 antibiotics. Therefore, in terms of biosafety, the presence of antibiotic resistance strains in the food chain has raised concerns that the treatment of human infections will be compromised.